The Dialectical Relationship Between Religion and Science: A Study of the Paradigms of Islamic Science at the State Islamic University, Syarif Hidayatullah, Jakarta - Awaliyah Fitri, Sofia Ratna; Natsir, Nanat Fatah; Haryanti, Erni (Jurnal Penelitian Pendidikan Islam, 2022)
The research investigates the paradigmatic dialectic and the relationship between religion and science in Indonesia. However, because the topic is quite broad, this research focuses on integrating science as a science paradigm at State Islamic University Syarif Hidayatullah (UIN Syahid). This research is qualitative research with descriptive-explanatory analysis of written sources, which is also library research. This study found that the concept, foundation, and orientation of scientific integration at UIN Syahid showed its uniqueness. On the one hand, UIN Syahid is the pioneer and the first Islamic university in the transformation of IAIN/STAIN to UIN. Still, on the other hand, UIN Syahid is also the only UIN that has not uniformized the implementation and practice of scientific integration at the level of lecturers and students. Therefore, the absence of unification of the implementation and practice of scientific integration is a weakness on the one hand but also a strength and an advantage on the other. However, UIN Syahid has developed the concept of scientific integration at a philosophical level, although it does not express its integration pattern in certain symbols, visualizations, and terminology.